High‐Performance Ambipolar Polymers Based on Electron‐Withdrawing Group Substituted Bay‐Annulated Indigo. (2nd January 2019) - Yang, Jie; Jiang, Yaqian; Tu, Zeyi; Zhao, Zhiyuan; Chen, Jinyang; Yi, Zhengran; Li, Yifan; Wang, Shuai; Yi, Yuanping; Guo, Yunlong; Liu, Yunqi
Abstract: For donor–acceptor conjugated polymers, it is an effective strategy to improve their electron mobilities by introducing electron‐withdrawing groups (EWGs, such as F, Cl, or CF3 ) into the polymer backbone. However, the introduction of different EWGs always requires a different synthetic approach, leading to additional arduous work. Here, an effective two‐step method is developed to obtain EWG substituted bay‐annulated indigo (BAI) units. This method is effective to introduce various EWGs (F, Cl, or CF3 ) into BAI at different substituted positions. Based on this method, EWG substituted BAI acceptors, including 2FBAI, 2ClBAI, and 2CF3 BAI, are reported for the first time. Furthermore, four polymers of PBAI‐V, P2FBAI‐V, P2ClBAI‐V, and P4OBAI‐V are developed. All the polymers show ambipolar transport properties. Particularly, P2ClBAI‐V exhibits remarkable hole and electron mobilities of 4.04 and 1.46 cm 2 V −1 s −1, respectively. These mobilities are among the highest values for BAI‐based polymers. Abstract : Here, an effective two‐step method is developed to obtain an electron‐withdrawing group (EWG) substituted bay‐annulated indigo (BAI) units. Four polymers, PBAI‐V, P2FBAI‐V, P2ClBAI‐V, and P4OBAI‐V, are developed by this method. Particularly, P2ClBAI‐V exhibits remarkable hole and electron mobilities of 4.04 and 1.46 cm 2 V −1 s −1, respectively. These mobilities are among the highest values for BAI‐based polymers.